Pediatric colonic inflammatory myofibroblastic tumor presenting as colo-colonic intussusception: A case report and review of the literature - Jingjing Li Sherman; Armine Darbinyan; Margret S. Magid; Phat Ong; Barry Weissman; Keith Benkov; Aaron M. Lipskar (Elsevier, 2015)
Inflammatory myofibroblastic tumors (IMTs) are rare tumors of intermediate biologic potential most often reported in children. Histologic characteristics of IMT include spindle cell proliferation with chronic inflammatory cell infiltrate. IMTs can occur anywhere in the body but are most commonly reported in lung, bowel mesentery, and liver. Nonmesenteric alimentary IMTs are exceedingly rare. We present the second case of colonic IMT presenting as colo-colonic intussusception in a child. The patient is a 12-year-old female who presented with vague abdominal pain for three months. Her workup revealed an intraluminal mass in the descending colon on both CT and colonoscopy. Intraoperatively, the mass was seen causing colo-colonic intussusception. Laparoscopic segmental colon resection was performed, and the patient did well postoperatively. Histology and immunohistochemistry of the mass confirmed IMT.